Viridiana - Pérez Galdós, Benito 1843-1920; Pitaluca, Gustavo; Pérez Galdós, Benito 1843-1920 (The Criterion Coll., 2006)
"Novice nun Viridiana does her utmost to maintain her Catholic principles, but her lecherous uncle and a motley assemblage of paupers force her to confront the limits of her idealism"--Container.
Enth. Special Edition features. - New restored high-definition digital transfer
Aspect ratio 1.66:1, 16:9 widescreen. - New, restored high-definition digital transfer
Orig.: Spanien, Mexiko 1961. - Früheres Copyright 1991
Enth. new video interviews with actress Silvia Pinal and author Richard Porton ; excerpts from a 1964 episode of "Cinèastes de notre temps" on Luis Buñuel's early career ; a booklet featuring Michael Wood and an interview with Buñuel
Keywords: Catholic women -- Spain -- Drama; Lust -- Drama; Monasticism and religious orders for women -- Drama; Novitiate -- Drama; Spanien; Feature films; Fiction films; Foreign films; Melodrama